2017
DOI: 10.1007/s40750-017-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Aging: Masked Age Primes Influence Effort-Related Cardiovascular Response in Young Adults

Abstract: Based on the Implicit-Affect-Primes-Effort model and evidence that aging is associated with cognitive difficulties, this experiment investigated the effect of masked age primes on young adults' effort-related cardiovascular response during a mental arithmetic task. We predicted that elderly primes should activate the aging stereotype and thus render the performance difficulty concept accessible, while youth primes should activate the performance ease concept-similarly, as affect primes do. The accessible diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In easy and moderately difficult tasks, participants mobilized higher effort when they were exposed to briefly flashed sadness or fear primes than when they processed anger or happiness primes (e.g., Chatelain & Gendolla, 2015;Gendolla & Silvestrini, 2011;Lasauskaite, Gendolla, & Silvestrini, 2013;Silvestrini & Gendolla, 2011). Corresponding effects were recently found for the implicit activation of the aging vs. juvenility concept during cognitive performance (e.g., Zafeiriou & Gendolla, 2018). These findings support the predictions of the Implicit-Affect-Primes-Effort (IAPE) model (Gendolla, 2012(Gendolla, , 2015, which posits that implicitly processed affective stimuli influence the effort people mobilize during cognitive tasks via their impact on experienced task demand.…”
Section: Introductionmentioning
confidence: 82%
“…In easy and moderately difficult tasks, participants mobilized higher effort when they were exposed to briefly flashed sadness or fear primes than when they processed anger or happiness primes (e.g., Chatelain & Gendolla, 2015;Gendolla & Silvestrini, 2011;Lasauskaite, Gendolla, & Silvestrini, 2013;Silvestrini & Gendolla, 2011). Corresponding effects were recently found for the implicit activation of the aging vs. juvenility concept during cognitive performance (e.g., Zafeiriou & Gendolla, 2018). These findings support the predictions of the Implicit-Affect-Primes-Effort (IAPE) model (Gendolla, 2012(Gendolla, , 2015, which posits that implicitly processed affective stimuli influence the effort people mobilize during cognitive tasks via their impact on experienced task demand.…”
Section: Introductionmentioning
confidence: 82%
“…Moreover, extending our research on implicit influences on effort mobilization, Silvestrini (2015) found that high monetary incentive also increased effort-related cardiovascular responses of participants who implicitly processed pain-related words vs. control words during a difficult cognitive task. Likewise, Zafeiriou and Gendolla (2017) found a corresponding effect of monetary incentive for implicitly processed aging (vs. youth) primes in a difficult task (see also Zafeiriou & Gendolla, 2018). Those studies extended the applicability of the IAPE model logic in that they reasoned that both pain and aging are associated with cognitive performance difficulties.…”
Section: The Role Of Success Incentivementioning
confidence: 87%